Ujian Nasional, Dulu, Kini dan yang Akan Datang: Tinjauan Normatif - Muntholi’ah, Muntholi’ah (Nadwa, 2013)
The policy of the National Examination (UN) continues to get criticism from education experts, practitioners, as well as various elements of society. With the problems happen in the implementation of National Examination, it can be af-firmed that the impacts of its implementation are more harmful than the objec-tives to be achieved. Considering the imbalances and disadvantages of the Na-tional Examination implementation, the government through the Ministry of Education should have to be more thoughtful and immediately review the policy comprehensively. Thus, the purpose of education should be tailored to the inter-ests of Indonesia, which is stated and defined in the the National Education Law No. 20/ 2003 on National Education System Chapter II, Article 3.